Effect of poly(ε‐caprolactone) and titanium ( IV ) dioxide content on the UV and hydrolytic degradation of poly(lactic acid)/poly(ε‐caprolactone) blends - Adriaan Stephanus Luyt (14777044) (2023)
The effect of accelerated weathering degradation on the properties of poly(lactic acid) (PLA)/poly(ε-caprolactone) (PCL) blends and PLA/PCL/titanium (IV) dioxide (TiO2) nanocomposites are presented in this paper. The results show that both polymers are susceptible to weathering degradation, but their degradation rates are different and are also influenced by the presence of TiO2 in the samples. Visual, microscopic and atomic force microsocpy observations of the surface after accelerated weathering tests confirmed that degradation occurred faster in the PLA/PCL blends than in the PLA/PCL/TiO2 nanocomposites. The X-ray diffraction results showed the degradation of PCL in the disappearance of its characteristic peaks over weathering time, and also confirmed that PLA lost its amorphous character and developed crystals from the shorter chains formed as a result of degradative chain scission. It was further observed that the presence of TiO2 retarded the degradation of both PLA and PCL. These results were supported by the differential scanning calorimetry results. The thermogravimetric analysis results confirmed that that PLA and PCL respectively influenced each other's thermal degradation, and that TiO2 played a role in the thermal degradation of both PLA and PCL. The tensile properties of both PLA/PCL and PLA/PCL/TiO2 were significantly reduced through weathering exposure and the incorporation of TiO2.  Other Information Published in: Journal of Applied Polymer Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/app.51266